Velopharyngeal anatomy in 22q11.2 deletion syndrome: a three-dimensional cephalometric analysis. - Ruotolo RA; Veitia NA; Corbin A; McDonough J; Solot CB; McDonald-McGinn D; Zackai EH; Emanuel BS; Cnaan A; LaRossa D; Arens R; Kirschner RE (Cleft Palate Craniofacial Journal, 2006)
Objective: 22q11.2 deletion syndrome is the most common genetic cause of velopharyngeal dysfunction (VPD). Magnetic resonance imaging (MRI) is a promising method for noninvasive, three-dimensional (3D) assessment of velopharyngeal (VP) anatomy. The purpose of this study was to assess VP structure in patients with 22q11.2 deletion syndrome by using 3D MRI analysis. Design: This was a retrospective analysis of magnetic resonance images obtained in patients with VPD associated with a 22q11.2 deletion compared with a normal control group. Setting: This study was conducted at The Children's Hospital of Philadelphia, a pediatric tertiary care center. Patients, Participants: The study group consisted of 5 children between the ages of 2.9 and 7.9 years, with 22q11.2 deletion syndrome confirmed by fluorescence in situ hybridization analysis. All had VPD confirmed by nasendoscopy or videofluoroscopy. The control population consisted of 123 unaffected patients who underwent MRI for reasons other than VP assessment. Interventions: Axial and sagittal Ti- and T2-weighted magnetic resonance images with 3-mm slice thickness were obtained from the orbit to the larynx in all patients by using a 1.5T Siemens Visions system. Outcome Measures: Linear, angular, and volumetric measurements of VP structures were obtained from the magnetic resonance images with VIDA image-processing software. Results: The study group demonstrated greater anterior and posterior cranial base and atlanto-dental angles. They also demonstrated greater pharyngeal cavity volume and width and lesser tonsillar and adenoid volumes. Conclusion: Patients with a 22q11.2 deletion demonstrate significant alterations in VP anatomy that may contribute to VPD.